Trend of leptospirosis and its association with meteorological factors in Thrissur district, Kerala - Premdas, Alok Kanjhoor; Areekal, Binu; Sukumaran, Sudhiraj Thiruthara; Raj Kunnumel Kandi, Ashwin (International Journal Of Community Medicine And Public Health, 2019)
Background: Leptospirosis is a common zoonosis caused by bacteria, Leptospira. The core determinants of the disease are the presence of carrier animals, environmental factors and the interaction between man, carrier and the environment. Understanding the type of relation between these factors and leptospirosis will help in controlling the disease. The current study intends to find the trend of leptospirosis cases, to forecast the disease and to correlate number of cases of leptospirosis with meteorological factors. Methods: The data of leptospirosis cases and the meteorological factors in Thrissur district were collected and entered in MS- Excel and statistical analysis was done using SPSS-16.0. For analysing the trend and to forecast the same, time series analysis method was used. The correctness of the model was tested using Ljung-Box statistics. Results: Time series chart, autocorrelation and partial autocorrelation show leptospirosis follows a seasonal trend. Forecasting of leptospirosis cases from July 2018 to May 2019 made by the model matched with original number reported in Thrissur district. Cross correlation of total rainfall and total rainy days showed that leptospirosis peak approximately 1 month after the onset or together with the rain (lag-1 and 0, r0.471 and 0.380 for total rainfall, lag-1 and 0, r0.501 and 0.469 for total rainy days). Humidity positively affects number of leptospirosis cases (lag-1 and 0, r0.464 and 0.435). June to October, seasonally adjusted factor (SAF) was >100% with highest SAF in August (202.2%). Conclusions: Leptospirosis shows a seasonal trend with more cases in June to October and correlates with change in meteorological factors of the region.